(3eKdK bjGOI GdGbJUGO GdYGdejs (3UfOhb GdfbO GdOhdj,GdHfc GdOhdj,efXeI GdJLGQI GdYGdejIs - (3Mdej(B, (3NGdO SYO RZdhds ((3GdchjJs (3LGeYI GdchjJs, 2002)
(3UfOhb GdfbO GdOhdj,GdHfc GdOhdj,EJaGbGJ GdLGJ hefXeI GdJLGQI GdYGdejI,GdefXeGJ GdOhdjI GdEbJUGOjI hOhQgG GdbjGOjs
Keywords: (3UfOhb GdfbO GdOhdjs; (3efXeI GdJLGQI GdYGdejIs